ANALISIS PENYELESAIAN SENGKETA WAKAF DALAM PERSPEKTIF HUKUM PERADILAN AGAMA DI INDONESIA - Nisa, Khoiru; Attin, Sepvita Nur; Novitasari, Anggita; Nasoha, R. Ahmad Muhamad Mustain (AL HUKMU: Journal of Islamic Law and Economics, 2024)
Land is closely related to human life, making people think that land is capital in life in the world and will forever always be connected. Because humans really need land, it isi undeniable that there are many problems about land in life such as land disputes. An example is waqf land disputes that often occur in Indonesia. Waqf as the concept of giving property for the benefit and needs of society in the context of worship. Therefore, a way or method is needed in resolving waqf disputes under state law. Waqf dispute resolution can be done in litigation and non-litigation, based on Law No. 41 of 2004 concerning waqf so that all activities regarding waqf can run orderly and efficiently.